Pengaruh Electronic Word Of Mouth, Social Media Marketing, Harga Terhadap Keputusan Pembelian Marketplace Tokopedia - Tarigan, Purnaya Sari; Matakena, Simon; Sairdama, Syusantie Sylfia; Roy, Marloza; Nugraha, Aat Ruchiat (Journal of Business and Economics Research (JBE), 2023)
The lifestyle of the digital era and high levels of activity means that society in general is increasingly developing and has undergone changes in making purchasing decisions by determining how to shop online to meet consumer needs. Technological advances have made Tokopedia, which provides various needs or requirements, a marketplace of choice in society. Electronic word of mouth, social media marketing and price are believed to be able to influence plans to purchase a product, resulting in purchasing decisions. This research was conducted with the aim of finding out the influence of electronic word of mouth, social media marketing and price on Tokopedia marketplace purchasing decisions. The type of research used is quantitative. The sample method was non-probability sampling with purposive sampling, data analysis using IBM SPSS Statistics 26. The sample used was 100 students who met the research criteria who had made purchases from the Tokopedia marketplace. The data collection method uses a questionnaire with likert scale. The data collection technique uses a questionnaire whose validity and reliability have been tested. The data analysis technique used in this research is multiple linear regression. The results of the analysis show that partially, electronic word of mouth, social media marketing and price have a significant positive influence on purchasing decisions. The results of the Adjusted R Square value are shown to be 45.2%. Simultaneous results showed that the variables electronic word of mouth, social media marketing and price had a positive and significant influence on purchasing decisions.